FAKTOR - FAKTOR YANG MEMPENGARUHI BRAND LOYALTY - AULIA ARIEF NASUTION (LP2MTBM MAKARIOZ, 2022)
This study aims to analyze the influence of brand awareness, brand image, and brand satisfaction on brand loyalty. Datacollection is done by survey method with questionnaires. The survey was conducted on 100 matic motorcycle users inMedan City. Primary data is obtained through the dissemination of questionnaires. Hypothesis testing in this study usedModerate Regression Analysis. The results showed that brand satisfaction affects brand loyalty. While the variable brandexperience, brand image and brand awareness have no significant effect on brand loyalty.